Promoting scopolamine biosynthesis in transgenic Atropa belladonna plants with pmt and h6h overexpression under field conditions - Xia, Ke (Plant physiology and biochemistry : PPB, 2016)
Copyright © 2016 Elsevier Masson SAS. All rights reserved.